The Women’s Oral History Project at Columbia Law School - Bagnall, Whitney S. (Columbia Journal of Gender and Law, 2001)
Inspiration for undertaking an oral history project centering on the lives of women graduates of Columbia Law School came as a direct result of two events. The first was a panel sponsored by the Women’s City Club in New York entitled “Success Stories: Women Graduates of Columbia Law School.” Speaking at that event in March 1994 were Edith Spivack ’32, Ida Klaus ’31, Honorable Priscilla Hall ’73, Honorable Kristin Booth Glenn ’66, Lynn Hecht Schafran ’74, and Susan B. Lindenauer ’64. Interest and energy sparked by this panel carried over to a second event: the formation of the Alumnae of Columbia Law School in 1996. Women graduates of the Law School from across the country held meetings in the spring and fall of that year to establish an organization that would increase the standing of women lawyers in the profession. The Alumnae organized specific committees to carry out their stated mission “to support and enhance the professional development of the women of Columbia Law School.” While many of these committees focused on career development and advancement, mentoring, careers in public interest law, issues concerning women of color, and flexible work arrangements, one committee took a look backwards over the seventy-year span that women have been attending the Law School. This committee on the Celebration of the Admission of Women to Columbia Law School is coordinating plans for the seventy-fifth anniversary celebration of the admission of women to CLS, which will be celebrated in 2002. To recognize and honor the manifold accomplishments of the Law School’s earliest women graduates, the idea of collecting oral histories of these women offered an immediate opportunity to capture stories of their varied careers begun at a time when few women entered the legal profession. In the fall of 1996, Jane Bickford, then Associate Dean for Alumni/ae Relations, sent out letters to women graduates announcing plans for an oral history project to “preserve the stories and voices” of Columbia Law’s alumnae. Response to her letter was both gratifying and strong. The Women’s Oral History Project, ably chaired by Susan B. Lindenauer ’64 and Anne E. Cohen ’85, was launched with considerable energy and skill.